A start-up optimization strategy of a hydroelectric generating system: From a symmetrical structure to asymmetric structure on diversion pipes. (December 2021) - Lei, Liuwei; Li, Feng; Kheav, Kimleng; Jiang, Wei; Luo, Xingqi; Patelli, Edoardo; Xu, Beibei; Chen, Diyi
Abstract: This study focuses on the start-up optimization strategies for a Hydroelectric Generating System (HGS). A mathematical model of HGS to describe the complex hydraulic coupling relationship, between the water diversion pipes, the hydro-turbine, the governor and the generator, is proposed. This allows to accurately describe the start-up process and identifying the effect of successive start-up time interval ( ΔT ) and the pipe structure on the water head and the rotational speed of HGS. The result shows that the successive start-up strategy with ΔT = 9s maximally reduces the water head fluctuation of units #1 and #2 by 30.94% and 25.77% compared with the simultaneous start-up strategy when the branch pipe is symmetric. For the asymmetric branch pipe, the unit behind branch B# starts up first is beneficial to reduce the water head fluctuation of the unit behind branch #A when the flow inertia time constant of branch #A is larger. Finally, the parameters of the start opening as well the PID governor parameters are optimized by a multi-objective particle swarm optimization for the asymmetric pipe in order to minimize the unit speed overshoot and the speed rise time. These results in this work provide a theoretical guidance for the selection of optimal start-up strategy in the case of symmetric and asymmetric HGS branch pipe structures. Highlights: A hydroelectric generating system is established, which can describe the start-up process. The optimization algorithm is applied to the start-up process of hydro-turbine. The optimal start-up strategy of hydro-turbine with symmetric or asymmetric pipe are analyzed. The work can improve the start-up quality of hydro-turbine in practical engineering.